ANALISIS GAYA BAHASA DALAM LIRIK LAGU ALBUM BILA TIBA OST SANG KIAI GRUP BAND UNGU DAN IMPLIKASINYA SEBAGAI BAHAN PEMBELAJARAN APRESIASI PUISI DI SMP - Dema Tesniyadi (Universitas Sultan Ageng Tirtayasa, 2016)
This study discusses the style of language in the lyrics of the song album When Arrive Ost Sang Kiai Band Purple and Implications For Learning Materials Poetry Appreciation in junior high. The purpose of this study was to describe (1) the language style in the song lyrics Purple; (2) the function of the use of the language style lyrics band Purple, (3) the relevance of the lyrics band Purple as a learning material appreciation of poetry in junior high, and (4) learning poetry appreciation in junior high school with learning materials lyrics band Purple. The data source of this research is the album When Arrive Ost Sang Kiai (2014). Objects and research focus on the types, functions, and relevance Purple song lyrics as a learning material appreciation of poetry in junior high school, as well as find alternative learning poetry appreciation in junior high school with learning materials lyrics Purple. Refer to the data collection method and record. In analyzing the data, the content analysis method. The results of the study presented by informal methods. The results of this study: (1) the lyrics band Purple uses a variety of stylistic comparison (allegory, allusion, pars pro toto, synesthesia, and hyperbole), style assertion (preterito, euphemism, repetition, and ellipses), and stylistic contradictions (oxymoron); (2) that serves to enhance the sound, creating a certain mood feeling state, evokes the atmosphere and a certain impression, and strengthening effect on the track, which can make the listener impressed by the song that conveyed the author; (3) relevant Purple song lyrics and used as a learning material appreciation of poetry in class IX SMP either because the lyrics contain a lot of style and full of positive values, as well as having a harmonious rhythm; (4) learning poetry appreciation to the material in the Junior Purple song lyrics done by having four stages: planning, implementation, and evaluation of learning and reflection.